Comparative effects of high-intensity and sprint interval training on cardiorespiratory fitness and body composition: a systematic review with meta-analysis - Zhang, Da; Dong, Jie; Hou, Chien-Wen; Wang, Jie-ping (Frontiers in Physiology, 2025)
BackgroundInterval training modalities, including high-intensity interval training (HIIT) and sprint interval training (SIT), are widely recognized for their efficiency and health benefits. However, it remains unclear how baseline fitness levels influence the differential effects of HIIT and SIT on key health-related outcomes.ObjectiveThis meta-analysis aims to compare the effects of HIIT and SIT on cardiorespiratory fitness (CRF) and body fat mass, with subgroup analyses based on participants’ health and training status.MethodsNine randomized controlled trials (n = 666) were included. Primary outcomes were changes in VO2max/VO2peak and body fat percentage. Data were synthesized using standard mean difference (SMD) or weighted mean difference (WMD), with subgroup analyses stratified by population type (healthy/trained vs. overweight/obese). This review was registered in PROSPERO (CRD420251016362; registered on 15 March 2025).ResultsBoth HIIT and SIT significantly improved CRF (SMD = 1.54; 95% CI: 0.89–2.18; p < 0.00001) and reduced body fat mass (WMD = −3.45%; 95% CI: −5.04 to −1.87; p < 0.0001) compared to control. Subgroup analyses revealed that HIIT was more effective in improving CRF in overweight/obese individuals (SMD = −0.97; p = 0.0004), while SIT was more effective in reducing fat mass among healthy or trained populations (WMD = 5.85; p < 0.00001).ConclusionBoth HIIT and SIT are effective interventions for enhancing CRF and reducing body fat, but their relative efficacy may depend on participants’ baseline health status. HIIT appears optimal for individuals with lower fitness levels, while SIT may be preferable for time-efficient fat reduction in trained populations. Tailoring interval training prescriptions to individual characteristics is recommended.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251016362.